Punishment - 3 analytical threads and violence they produce - Eynon, T.G. (Economic & Social Studies, 1974)
In so far as punishment is concerned, it appears to me that the main features are to be found in an examination o f political dialogue; legal philosophy; and empirical research. It is as though the two cultures of Professor Snow have emerged into the three relatively isolated sub-cultures of punishment, that is politics, philosophy and research.
Keywords: Punishment; Violence